2019
DOI: 10.1186/s12885-019-5314-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of homologous recombination repair pathway indicates susceptibility for olaparib treatment in malignant pleural mesothelioma in vitro

Abstract: BackgroundMalignant pleural mesothelioma (MPM) is a tumour arising from pleural cavities with poor prognosis. Multimodality treatment with pemetrexed combined with cisplatin shows unsatisfying response-rates of 40%. The reasons for the rather poor efficacy of chemotherapeutic treatment are largely unknown. However, it is conceivable that DNA repair mechanisms lead to an impaired therapy response. We hypothesize a major role of homologous recombination (HR) for genome stability and survival of this tumour. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
0
21
0
3
Order By: Relevance
“…For example, we have reported that PARP inhibition (by olaparib and niraparib) sensitized tumor cells that have been exposed to ionizing radiation by producing a more robust senescent response associated with increased DNA double-stranded damage [130]. These results were recently confirmed by showing that olaparib, the first FDA-approved PARP inhibitor, results in a robust senescent response (rather than apoptosis) when preceded by genotoxic stress induced by cisplatin or pemetrexed [146].…”
Section: Parp Inhibitorsmentioning
confidence: 87%
“…For example, we have reported that PARP inhibition (by olaparib and niraparib) sensitized tumor cells that have been exposed to ionizing radiation by producing a more robust senescent response associated with increased DNA double-stranded damage [130]. These results were recently confirmed by showing that olaparib, the first FDA-approved PARP inhibitor, results in a robust senescent response (rather than apoptosis) when preceded by genotoxic stress induced by cisplatin or pemetrexed [146].…”
Section: Parp Inhibitorsmentioning
confidence: 87%
“…87 Likewise, BAP1 mutations have also been linked to cellular sensitivity to apoptosis following treatment with the PARP inhibitor olaparib. 88 Trials examining PARP inhibitors in patients with these cellular defects are currently ongoing and eagerly awaited.…”
Section: Future Directionsmentioning
confidence: 99%
“…BAP1 funciona para estabilizar el BRCA-1 y promover el reclutamiento dependiente de poli (ADP-Ribosa) del complejo de poliquial deubiquitinasa PR-DUB a los sitios de daño del ADN. [104][105][106] Esta actividad depende de la actividad de la deubiquitinasa y de la fosforilación de BAP1. 107 Las mutaciones BAP1, que siempre parecen manifestarse como pérdida de función, disminuyen los niveles de BRCA-1 e inhiben la reparación del ADN de doble cadena.…”
Section: Swi/snfunclassified
“…Estas estrategias podrían mejorar las respuestas a cisplatino/pemetrexed en pacientes con MPM. 106 Estos hallazgos, junto con las observaciones recientes del microambiente, tienen un impacto en el resultado de los pacientes con MPM para una combinación convincente de inmunoterapias epigenéticas para estas neoplasias. [106][107] conclusIones El MPM es una enfermedad con incidencia baja, pero con un comportamiento agresivo, cuya supervivencia no va más allá de 12 meses una vez hecho el diagnóstico.…”
Section: Swi/snfunclassified
See 1 more Smart Citation